Afrikai vasutak kínai segítséggel – Kinek éri meg? - Bucsky, Péter (Afrika Tanulmányok / Hungarian Journal of African Studies, 2018)
In Kenya and Ethiopia the new railways financed by Chinese loans and built by Chinese technology and by Chinese companies are already in service. Many people see these as a boost for development, but both of them are upgrades of already existent lines. It is questionable whether or not the countries will be able to repay the costs of these investments, and the railways can generate enough additional growth that can finance the loans. There are also other options for railway development than Chinese loans and it is interesting to analyse which option is the most straightforward and beneficial for African countries from the current examples and potentials for railway development. From the analysis we can see that Chinese loans do not seem to be the best solution, as countries are taking very high debt for projects with risky returns. The example of Tanzania shows that open international procurement and competition can lead to cheaper and sustainable railway development in Africa, as opposed to Chinese loan-driven investment schemes.